Marco metodológico para el desarrollo de proyectos de mejoramiento y rediseño de procesos (2019)
Over the last decades, methodologies for the improvement and redesign of processes have come from stastical control of projects, from the PHVA cycle, from the concept of Porter’s value chain (1985) passing through re-engineering, six sigma, BPM, among others. Some organizations have applied these methodologies and performance models. However, none of these provides a general methodological framework where systematic steps may be taken by a company in order to ascertain how to develop a project appropriately when change in processes is involved, regardless of the methodology or performance model implemented. In this article a methodological framework is presented that has been developed as the result of the comparison of some of the existing methodologies and the work done by the author as a consultant. This methodology has been designed to be applied by work teams of companies in charge of the re-design and improvement projects on processes.